Previously identified protein of uncertain function is karyopherin alpha and together with karyopherin beta docks import substrate at nuclear pore complexes. - Moroianu, J (1995)
Previously, we had purified a cytosolic protein complex, termed karyopherin, that functions in docking import substrate at the nuclear envelope in digitonin-permeabilized cells and also had molecularly cloned and sequenced its 97-kDa beta subunit. We now report that the karyopherin alpha subunit is the previously identified protein NPI-1/SRP-1 of hitherto uncertain function. Using purified recombinant karyopherin alpha or beta subunit, we showed that neither karyopherin alpha nor karyopherin beta alone was sufficient for docking of import substrate at the nuclear envelope. Docking occurred only when both subunits were present. Moreover, docking of import substrate by the two recombinant karyopherin subunits was productive, as it led to nuclear internalization of the docked substrate in the presence of additional, previously characterized cytosolic factors. In a binding assay using immobilized karyopherin alpha and beta subunits and import substrate as a ligand, we found that only karyopherin alpha bound ligand. We suggest that karyopherin beta functions as an adaptor that binds both to karyopherin alpha and to any of a large number of docking sites that are represented by a repetitive peptide motif containing nucleoporins on both the cytoplasmic and nucleoplasmic side of the nuclear pore complex (NPC), bidirectionally ferrying a complex of karyopherin alpha-substrate across the NPC.